Reexamination of the determinants of master student satisfaction - Nik Mat, Nik Kamariah; Ahmad, Nor Hayati; Ismail, Rusmawati (Universiti Utara Malaysia, 2004)
In pursuing world class university objective, UUM is continuously enhancing the quality standard of its programs. One of the ways to increase quality of higher education is through identifying the student satisfaction determinants. Previous study conducted in similar topic (Nik Mat, Ahmad, & Ismail, 1999) shows that lecturer, language and administration contributed significantly to overall master student's satisfaction while language, administration and core curriculum significantly influenced recommendation. The objectives of this study are (i) to determine the factors contributing to the students' satisfaction and recommendation and (ii) to compare the results of this study with the previous study. The study investigates the relationships between five predictor variables (infrastructure, core curriculum, lecturer, language and administration), and two criterion variables (satisfiction and recommendation). A three-page questionnaire was distributed to 150 masters' students. 71 responses (47% response rate) were obtained. The findings indicate that the overall satisfaction towards the Masters programs is determined significantly by infrastructure and administration. Administration is again found to be significantly related to recommendation. The implications of the findings are discussed.